Barriers to information and communication technology (ICT) adoption and use amongst SMEs: a study of the South African manufacturing sector - Pillay, Priyal (My University, 2016)
This paper aims to look at the barriers of ICT adoption amongst Small to Medium Enterprises (SMEs) in South Africa, specifically in the high growth-manufacturing sector. The population of the study is comprised of manufacturing SME owners and managers in Gauteng, South Africa. The objectives of this study are threefold. Firstly, it aims to establish which ICTs SMEs are currently making use of in South Africa. Secondly, it will analyse the perceived value added to SMEs through ICT adoption. And thirdly, the study endeavours to unearth the various barriers faced by SMEs when adopting ICTs. The research consists of data collection from 81 SMEs in the manufacturing sector in Gauteng, South Africa, by means of an online questionnaire. The data was analysed through a variety of statistical techniques covering both descriptive statistics and multivariate analysis. The following conclusions were reached:  Three barriers examined are significantly important to the adoption of ICTs, namely lack of existing hardware, immediate return on investment (ROI), and lack of infrastructure.  The perceived value of ICT has a positive, significant relationship to ICT adoption.  The majority of SMEs still predominantly make use of general ICTs, with more advanced ICT use lagging behind significantly. The majority of respondents have Voice Over Internet Protocol (VoIP) phone services (69%), Internet access and e-mail (90%), as well as telephone (89%) and fax (82%) services as ICTs that have already been implemented.  The education level of the owner/manager has a significant, positive relationship with the level of ICT adoption, particularly amongst general-use ICT and production- integrating ICT.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Management (MMENVC) Johannesburg, February 2016
Keywords: Information technology--Management; Small business--Technological innovations--South Africa